Investigation of the variation of near-circular polarization in Scarabaeoidea beetles - McCall,MW; Carter,IE; Weir,K (Materials Today: Proceedings, 2017)
Variation in the reflection of circularly polarized light (CP) of a substantial number of beetles, of both the Hybosoridae and Scarabaeidae families, is discussed. Classifications of the spectral shapes were made for Cetonia aurata aurata beetles, which were related to variations within the chiral chitin structure and have been computationally modelled. It was seen that single peaked spectra were not the predominant spectral shape and that more complex structures are responsible for the spectra observed. Two structural perturbations methods to the single pitched structure are proposed to be responsible for the more complex spectral shapes. Further CP analysis of the genus rutelinae:Chrysina was undertaken with variations in broadband reflection observed within the optima species.